AN ANALYSIS OF FOREST AND LAND FIRE EXTINGUISHING IN INDONESIA INFLUENCED BY THE EL NINO PHENOMENON USING THE WATER BOMBING METHOD - Danar A.W Gautama; Petrisly Perkasa; Tuah (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2023)
Land and peat forest fires in Indonesia are a serious environmental problem, especially in the years that experience the El Nino phenomenon. El Nino causes dry and hot conditions that trigger fires. One of the methods used to extinguish fires is water bombing, which is spraying water from the air using planes or helicopters. The purpose of this study is to analyze the effectiveness and efficiency of the water bombing method in dealing with land and peat forest fires in Indonesia. This study uses secondary data from various sources, such as government reports, research institutions, mass media, and non-governmental organizations. The data is then analyzed using descriptive, comparative, and evaluative methods. The results of the study show that the water bombing method has some advantages, such as fast, flexible, and able to reach areas that are difficult to access. However, this method also has some disadvantages, such as expensive, risky, and less effective in extinguishing fire in the peat soil. Therefore, this study recommends that the water bombing method should be used as one part of a comprehensive fire control strategy, which involves prevention, detection, and recovery. This study also suggests the need for improved coordination, regulation, and innovation in the use of the water bombing method in Indonesia.